Hamka's Ethical Thought and the Transformation of the Islamic Education Curriculum in Indonesia - Muh Taofiq Abdul Wahab; Nuraini Nuraini; Ayu Wulansari; Siti Marpuah (JIE (Journal of Islamic Education), 2026)
The transformation of the Islamic education curriculum in Indonesia faces challenges in strengthening students' character development amid globalisation, social change, and various moral crises. This study aims to analyse the relevance of Buya Hamka's ethical thought in Falsafah Hidup to the transformation of the Islamic education curriculum in Indonesia. This study employs a literature review (library research) method using a figure-centered approach and conceptual analysis. Data were collected through documentation of Buya Hamka’s works and relevant scholarly literature, analysed thematically, and validated through source triangulation. The findings indicate that Buya Hamka positions ethics as a core element of education that must be internalised through a balance of rational and spiritual dimensions. His ethical thought is relevant to curriculum transformation through the integration of moral values into learning, the strengthening of experiential learning, the optimisation of teachers' roles as role models, and the development of character-oriented assessment systems. This study offers a framework for integrating Hamka's moral values into curriculum development. It highlights their potential contribution to forming insan kamil—individuals who are knowledgeable, morally upright, and responsive to contemporary challenges. The findings affirm that Buya Hamka’s thought remains relevant as a philosophical foundation for a holistic Islamic education curriculum.